How do you differentiate ${x^{\ln x}}$?
Answer
Verified
443.7k+ views
Hint: First express the given function in the form of $y = f\left( x \right)$. Then take logarithm on both sides of the equation to simplify it so as to make differentiation easier. Then differentiate both sides with respect to $x$ and make the substitution wherever required. Apply the chain rule of differentiation which is $\dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$ to differentiate the composite functions.
Complete step by step answer:
According to the question, we have to show how to differentiate the function ${x^{\ln x}}$.
Let this function be denoted as $y$. Then we have:
$ \Rightarrow y = {x^{\ln x}}{\text{ }}.....{\text{(1)}}$
If we take natural logarithm on both sides, we’ll get:
\[ \Rightarrow \ln y = \ln {x^{\ln x}}\]
We know the logarithmic formula $\ln {a^b} = b\ln a$. On applying this formula, we have:
\[ \Rightarrow \ln y = \ln x\ln x\]
This can be written as:
\[ \Rightarrow \ln y = {\left( {\ln x} \right)^2}\]
Now if we put $\ln x = t$, we’ll get:
\[ \Rightarrow \ln y = {t^2}\]
Differentiating this equation both sides with respect to $x$, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dx}}\left( {{t^2}} \right)\]
We know the chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$
Applying this rule for our function, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dt}}\left( {{t^2}} \right)\dfrac{{dt}}{{dx}}\]
We know the formulas of differentiation $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x}$ and $\dfrac{d}{{dx}}{x^2} = 2x$. Applying them, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2t\dfrac{{dt}}{{dx}}\]
Putting back the value of $t$, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x\dfrac{d}{{dx}}\left( {\ln x} \right)\]
Again applying the formula of differentiation, we’ll get:
\[
\Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x \times \dfrac{1}{x} \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{2y\ln x}}{x} \\
\]
Putting back the value of $y$ from equation (1), we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^{\ln x}}} \right) = \dfrac{{2{x^{\ln x}}\ln x}}{x}\]
This is the required differentiation.
Note: Whenever we have to differentiate a composite function, we always use chain rule of differentiation after substitution. This makes a complex looking function simple from where we can differentiate step by step. For example, consider the given composite function:
$ \Rightarrow y = f\left( {g\left( x \right)} \right)$
To differentiate this function, we’ll substitute $g\left( x \right) = t$, we will have:
$ \Rightarrow y = f\left( t \right)$
Now we can apply chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}f\left( t \right) \times \dfrac{{dt}}{{dx}}$
Now this differentiation is simple and we can do it step by step. After doing this, we can put back the value of $t$ to get the answer.
Complete step by step answer:
According to the question, we have to show how to differentiate the function ${x^{\ln x}}$.
Let this function be denoted as $y$. Then we have:
$ \Rightarrow y = {x^{\ln x}}{\text{ }}.....{\text{(1)}}$
If we take natural logarithm on both sides, we’ll get:
\[ \Rightarrow \ln y = \ln {x^{\ln x}}\]
We know the logarithmic formula $\ln {a^b} = b\ln a$. On applying this formula, we have:
\[ \Rightarrow \ln y = \ln x\ln x\]
This can be written as:
\[ \Rightarrow \ln y = {\left( {\ln x} \right)^2}\]
Now if we put $\ln x = t$, we’ll get:
\[ \Rightarrow \ln y = {t^2}\]
Differentiating this equation both sides with respect to $x$, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dx}}\left( {{t^2}} \right)\]
We know the chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$
Applying this rule for our function, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dt}}\left( {{t^2}} \right)\dfrac{{dt}}{{dx}}\]
We know the formulas of differentiation $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x}$ and $\dfrac{d}{{dx}}{x^2} = 2x$. Applying them, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2t\dfrac{{dt}}{{dx}}\]
Putting back the value of $t$, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x\dfrac{d}{{dx}}\left( {\ln x} \right)\]
Again applying the formula of differentiation, we’ll get:
\[
\Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x \times \dfrac{1}{x} \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{2y\ln x}}{x} \\
\]
Putting back the value of $y$ from equation (1), we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^{\ln x}}} \right) = \dfrac{{2{x^{\ln x}}\ln x}}{x}\]
This is the required differentiation.
Note: Whenever we have to differentiate a composite function, we always use chain rule of differentiation after substitution. This makes a complex looking function simple from where we can differentiate step by step. For example, consider the given composite function:
$ \Rightarrow y = f\left( {g\left( x \right)} \right)$
To differentiate this function, we’ll substitute $g\left( x \right) = t$, we will have:
$ \Rightarrow y = f\left( t \right)$
Now we can apply chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}f\left( t \right) \times \dfrac{{dt}}{{dx}}$
Now this differentiation is simple and we can do it step by step. After doing this, we can put back the value of $t$ to get the answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE